(untitled) (Archaeologia Adriatica, 2014)
The paper analyses the significance of the viewshed in the prehistoric landscape of the northern and central Velebit regions. Particular attention is dedicated to sites mentioned in academic literature as the central settlements of communities (the hillforts of Kuk in Senj, Gradina in Sveti Juraj and Drvišica in Karlobag) and to their positions in the visual landscape. To date, the literature has pointed to the strategic significance of these locations. Based on this, the author explores the possibilities of their visual control over the landscape, sea traffic, economically usable areas and other sites.